Germanium-on-silicon waveguides operating at mid-infrared wavelengths up to 85 μm - Nedeljkovic, Milos (2018)
We report transmission measurements of germanium on silicon waveguides in the 7.5–8.5 μm wavelength range, with a minimum propagation loss of 2.5 dB/cm at 7.575 μm. However, we find an unexpected strongly increasing loss at higher wavelengths, potential causes of which we discuss in detail. We also demonstrate the first germanium on silicon multimode interferometers operating in this range, as well as grating couplers optimized for measurement using a long wavelength infrared camera. Finally, we use an implementation of the “cut-back” method for loss measurements that allows simultaneous transmission measurement through multiple waveguides of different lengths, and we use dicing in the ductile regime for fast and reproducible high quality optical waveguide end-facet preparation.